(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate, through chemical and bacteriological parameters, the water quality from drinking fountains at a Federal Higher Education Institution, in different climatic periods. Total coliforms and Escherichia coli were quantified by the enzyme method of the defined substrate; heterotrophic bacteria by plating in depth in Plate Count Agar; pH and chlorine, using commercial kits. The research was conducted in two stages: the first one, referring to the initial analyses during the rainy season, with the verification of the presence of samples in disagreement with the current legislation; and the second, during the dry period, after the corrective measures adopted in function the results obtained in the first stage, totalling 89 samples in both stages, from 49 drinking fountains. In the first stage, bacteriological evaluations showed that 65.3 % of the samples were inadequate, while in the second, the failure rate was 20.4 %. The parameters evaluated in the two stages revealed that there was no significant result (p˃0.05) in relation to pH, total coliforms and Escherichia coli. Unlike what was observed for mesophilic aerobic and chlorine content (p<0.05), which are believed to have been influenced by climatic conditions, with higher rates of non-compliance in the first stage, that is, found in the rainy season. These findings demonstrate the existence of inadequate hygienic-sanitary conditions and the need of frequent monitoring of water quality, as well as the positive impact after the educational intervention and the adoption of preventive and corrective measures, aimed at the safety of the consumer community.